The advantages of a small European Monetary Union - Lukas Menkhoff; Friedrich L. Sell (Intereconomics, 1991)
The question whether European Monetary Union should include all the EC countries from the start or should initially be limited to a few core countries is again being discussed more intensely. What advantages would a small EMU have from an economic point of view? Which countries should be its founder members?
Keywords: 330; European Community